2022
DOI: 10.3390/antiox11122327
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective Effect of Anisomeles indica on Aspirin-Induced Gastric Ulcer in Mice

Abstract: Gastric ulcers are commonly seen in the upper gastrointestinal tract and may be related to the Helicobacter pylori infection and the use of aspirin, a nonsteroidal anti-inflammatory drug (NSAID). Typically, proton-pump inhibitors (PPIs) are used to treat gastric ulcers; however, adverse effects have emerged following long-term treatment. Natural medicines are used as alternative therapeutic agents in the treatment of gastric ulcers, with few side effects. Despite various reports on the anti-H. pylori and anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Although current therapy is effective in the treatment of peptic ulcers, it is notable that the disease still has a high prevalence and continues to be a health problem worldwide. In this way, it becomes necessary to investigate natural medicinal plants and their derivatives as alternatives for therapy and the minimization of side effects [2,27].…”
Section: Discussionmentioning
confidence: 99%
“…Although current therapy is effective in the treatment of peptic ulcers, it is notable that the disease still has a high prevalence and continues to be a health problem worldwide. In this way, it becomes necessary to investigate natural medicinal plants and their derivatives as alternatives for therapy and the minimization of side effects [2,27].…”
Section: Discussionmentioning
confidence: 99%
“…The patient's presentation with epigastric pain, nausea, and vomiting following high NSAID intake was suspicious of NSAID-induced gastrointestinal damage [ 14 ]. NSAIDs are known to compromise the gastric mucosal barrier, increasing the risk of ulcers [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The whole A. indica plant was obtained from the contractual farms of SYI Biotechnology (Taichung, Taiwan). A. indica extract was prepared as previously described [15] with minor modifications. The formulation of A. indica HP813 powder included soluble fiber from corn, xylo-oligosaccharides, and A. indica extract powder.…”
Section: Samplementioning
confidence: 99%
“…Anisomeles indica (L.) Kuntze, a plant of the genus Anisomeles in the family Lamiaceae [11,12], is a traditional herbal medicine commonly used in Taiwan. The results of recent studies have revealed that A. indica extracts have pharmacological activities, including anti-inflammatory activities, tumor cell growth inhibition, treatment of gastrointestinal and liver diseases, treatment of inflammatory skin diseases, and anti-H. pylori activities [13][14][15]. Previous studies have isolated some chemical constituents from A. indica, including apigenin, ovatodiolide, β-sitosterol, and acteoside [16,17].…”
Section: Introductionmentioning
confidence: 99%